Pola Penerapan Residensi Unggulan Melalui Pendekatan In-kind dan Matchmaking dalam Pengembangan Media Pembelajaran Seni Lintas Disiplin bersama Industri Kreatif Program Studi Pendidikan Seni Rupa - Eka Putri Surya; Abdul Rahman Prasetyo; Adinda Marcelliantika; Alby Aruna; Ginanjar Atma Wijaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The implementation pattern of flagship residencies through in-kind and matchmaking approaches in developing interdisciplinary art learning media with the creative industry at the Fine Arts Education Study Program aims to enhance the quality and relevance of art education. This program integrates in-kind contributions from the creative industry with a matchmaking process to create productive collaborations between students and industry practitioners. Methods include residency selection, interdisciplinary art project development, and evaluation of program outcomes and impacts. The results show an increase in students' practical skills and interdisciplinary understanding, as well as the enrichment of the fine arts education curriculum through direct input from the creative industry. The implementation of this pattern is expected to strengthen the synergy between education and industry, and produce innovative and applicable art learning media